PERAN CORE VALUE “AKHLAK” DALAM MENINGKATKAN KINERJA KARYAWAN PT KAI (PERSERO) DAOP 4 SEMARANG - Ahmad Nur Kalinggar; Febrianur Ibnu Fitroh Sukono Putra; Artha Febriana; Elia Resha Fatmawati (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2026)
Introductions: When faced with challenges in the transportation industry and the high demands of public services, PT KAI (Persero) applies the core values of "AKHLAK" as the foundation of its work culture. However, the effectiveness of internalizing these values in employee performance still requires empirical research to demonstrate it. This study aims to determine the influence of the AKHLAK principles (Trustworthy, Competent, Harmonious, Loyal, Adaptive, and Collaborative) on the performance of PT KAI (Persero) Daop 4 Semarang employees. Method: This study uses a quantitative approach, employing a survey. Primary data were collected through a Likert-scale questionnaire 1–5 distributed using physical paper to 149 respondents. The sampling technique used was saturated sampling, according to the criteria of being 21–60 years old, having a minimum education of high school or bachelor’s degree, having a work experience of 1 to 5 years, and having permanent employee status. Data analysis was carried out using multiple linear regression in SPSS. Result: The study indicates that the values of Trustworthy, Competent, Harmonious, and Adaptive have a positive and significant influence. However, two variables, Loyalty and Collaborative, were insignificant. This study contributes to strengthening literacy in values-based human resources in the state-owned enterprise sector and offers practical implications for optimizing a productive and sustainable work culture. Keywords: Attitude Toward Behavior, Behavioral Control, Perceived Stock Investment Intention, Subjective Norms